TI_GERICHTE 52.2018.148 vom 28. Februar 2018 , Revoca della licenza di condurre. Capacità di condurre. Obbligo di superare nuovi esami - TI Tribunale d'appello (2018)
Revoca della licenza di condurre. Capacità di condurre. Obbligo di superare nuovi esami